(untitled) (Estudos Japoneses, 1997)
This study shows the origins of the I novel and its differents interpretation. The term Contemplative Novel, first introduced by Kume Masao to better elucidate de I novel, gains a new interpretation with Itô Sei and Hirano Ken, resulting in a division of the terms.